Pendampingan Penilaian Autentik Berbasis Karakter untuk Guru Sekolah Dasar - Deny Setiawan; Apiek Gandamana; Nurhairani Nurhairani; Reh Bungana Beru PA (Universitas Medan Area, 2020)
Community service activities generally aim to develop character in developing the potential of students who have intelligence, personality and noble character. Through this activity to assist teachers in 104202 Bandar Setia Elementary School, Percut Sei District, Deli Serdang District in carrying out character-based authentic assessments. The model applied in the implementation of Community Service is carried out in several stages, namely: First, the stage of preparation with activities, (a) conducting socialization to teachers; (b) carrying out observations and interviews; (c) determining the schedule of activities; and (d) preparing facilities and infrastructure. Second, the implementation phase through, (a) Focus Group Discussion (FGD); (b) training and education for the preparation of authentic assessment instruments; and (c) assisting in the application of character-based authentic assessments. Third, the evaluation and reflection phase is an assessment of attitudes, skills and knowledge. Through this activity the teacher has character-based authentic assessment guidelines and the formation of the Teacher Working Group (KKG)